Three Practical Assignments for the Introductory Risk Management and Insurance Student. Issue 2 (21st October 2013) - Gatzlaff, Kevin M.
Abstract: I have developed, used, and refined an auto quote assignment, a life quote assignment, and a retirement analysis assignment that seem to communicate certain concepts well to the typical student enrolled in a risk management and insurance principles course. These assignments consist of worksheets requiring Internet research and a series of questions based on the answers discovered. Additionally, a short class discussion follows each of the three assignments to further ensure that students have achieved the primary learning objectives of each assignment. In their current form, these assignments are practical and require relatively minimal student and instructor time. Each could easily be expanded to accommodate students with advanced understanding and capability.